2008
DOI: 10.1073/pnas.0707318105
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of endocytic components yields insight into the process of nonendosymbiotic organelle evolution

Abstract: The process by which some eukaryotic organelles, for example the endomembrane system, evolved without endosymbiotic input remains poorly understood. This problem largely arises because many major cellular systems predate the last common eukaryotic ancestor (LCEA) and thus do not provide examples of organellogenesis in progress. A model is emerging whereby gene duplication and divergence of multiple ''specificity-'' or ''identity-'' encoding proteins for the various endomembranous organelles produced the divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
143
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(147 citation statements)
references
References 58 publications
(82 reference statements)
4
143
0
Order By: Relevance
“…Detection of the a-and b-subunit isoforms in the mass spectrometry ( Figure 3C) implies they are functionally equivalent to each other. Our recent study revealed that both AP1/2B1 and AP1/2B2 also interact with the m-subunit of AP-1 complex (ADAPTOR PROTEIN-1 MU-ADAPTIN2 [AP1M2]) (Teh et al, 2013), indicating a common use of the b-subunit isoforms by AP-1 and AP-2 as predicted (Boehm and Bonifacino, 2001;Bassham et al, 2008;Dacks et al, 2008). Coimmunoprecipitation assays demonstrated the weak interaction between AP-2 and CHC ( Figure 3D), implying that the AP-2 complex is transiently associated with clathrin during CCV formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of the a-and b-subunit isoforms in the mass spectrometry ( Figure 3C) implies they are functionally equivalent to each other. Our recent study revealed that both AP1/2B1 and AP1/2B2 also interact with the m-subunit of AP-1 complex (ADAPTOR PROTEIN-1 MU-ADAPTIN2 [AP1M2]) (Teh et al, 2013), indicating a common use of the b-subunit isoforms by AP-1 and AP-2 as predicted (Boehm and Bonifacino, 2001;Bassham et al, 2008;Dacks et al, 2008). Coimmunoprecipitation assays demonstrated the weak interaction between AP-2 and CHC ( Figure 3D), implying that the AP-2 complex is transiently associated with clathrin during CCV formation.…”
Section: Discussionmentioning
confidence: 99%
“…The Arabidopsis genome contains two homologous genes for each of the a and b subunits (Boehm and Bonifacino, 2001;Bassham et al, 2008;Dacks et al, 2008). This suggests that multiple sets of the different gene products are used to assemble the Arabidopsis AP-2 complex.…”
Section: Identification Of the Arabidopsis Ap-2 Complexmentioning
confidence: 99%
“…Endocytosis is known as a eukaryote-specific process by which cells internalize molecules from the plasma membrane and recycle them back to the surface or sort them to lysosomes for degradation (2). There is evidence that endocytosis must have been present in cells as far back as the last eukaryotic common ancestor (LECA) (3,4), but it has never been reported to occur in members of the domains Bacteria and Archaea. Recent hypotheses have placed the origin of endocytosis-like mechanisms as a primary step toward evolution of compartmentalization (3,4).…”
mentioning
confidence: 99%
“…There is evidence that endocytosis must have been present in cells as far back as the last eukaryotic common ancestor (LECA) (3,4), but it has never been reported to occur in members of the domains Bacteria and Archaea. Recent hypotheses have placed the origin of endocytosis-like mechanisms as a primary step toward evolution of compartmentalization (3,4). Surprisingly, subcellular compartmentalization is not a unique feature of the eukaryote cell: it has been discovered that a restricted group of bacteria belonging to the phyla Planctomycetes and Verrucomicrobia possess such compartmentalization (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…3) Dacks et al 2008) as a quinary feature of proteostasis folding biology is used by the eukaryotic cell to manage when and where a protein folds, when the fold should or should not be functional, and when it should be removed through degradation. The invention of the TPN as a unifying theme for eukaryotic membrane biology was a pivotal advance accelerating the evolability of unicelluar and multicellular Eukarya to not only optimize and integrate cell and organismal function for a particular niche, but to promote survival and fitness through natural selection (Darwin 1856(Darwin , 1867.…”
Section: Integrating Proteostasis and Membrane Trafficking Biologymentioning
confidence: 99%